Clinical Importance of Agrya Ausadha Aragvadha in the Management of Vicharchika: A Pharmacological Review - Manisha B; Suresh C; O.P. Singh; Sanjay Kumar Singh (International Journal of Ayurveda and Pharma Research, 2024)
In Ayurvedic clinical practice, Agrya ausadha are the first drug of choice for treatment of various diseases. Aragvadha, as an Agrya ausadha, is employed for its therapeutic benefits in both internal and external applications. It is notably used for Mridu virechana (mild purgation) and as a topical remedy for various types of Kustha. In Ayurvedic dermatology kustha has been taken as supreme word for all skin diseases. Vicharchika, classified as a Kshudra Kustha, is treated through the dual principles of Sodhana (purification) and Samana Chikitsa (pacification). The Majja (pulp) of Aragvadha is utilized for internal Sodhana therapy, while the leaves are applied externally as a paste for Samana Chikitsa. Preliminary findings indicate that Aragvadha meets the criteria for an ideal drug as per classical Ayurveda, given its accessibility (Bahuta), versatility in formulations (Anekvidhkalpana), and effectiveness (Yogatyam). Aragvadha, through its varied formulations, plays a crucial role in the Ayurvedic management of Vicharchika. Its use aligns with the principles of Sodhana and Samana Chikitsa, offering a comprehensive approach to treating this skin disorder. The study highlights the clinical significance of different parts of Aragvadha and supports its continued use in Ayurvedic dermatological practice.